2015
DOI: 10.1186/s13023-015-0314-x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid-Onset Obesity with Hypothalamic Dysfunction, Hypoventilation, and Autonomic Dysregulation (ROHHAD): exome sequencing of trios, monozygotic twins and tumours

Abstract: BackgroundRapid-onset Obesity with Hypothalamic Dysfunction, Hypoventilation, and Autonomic Dysregulation (ROHHAD) is thought to be a genetic disease caused by de novo mutations, though causative mutations have yet to be identified. We searched for de novo coding mutations among a carefully-diagnosed and clinically homogeneous cohort of 35 ROHHAD patients.MethodsWe sequenced the exomes of seven ROHHAD trios, plus tumours from four of these patients and the unaffected monozygotic (MZ) twin of one (discovery coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 35 publications
4
47
0
Order By: Relevance
“…The absence of PHOX2B mutations in individuals with ROHHAD, despite its clinical similarity to CCHS, suggests that other genes or regulatory sequences may be associated with autonomic function and NB pathogenesis (89).…”
Section: Inactivating Mutations In Phox2bmentioning
confidence: 99%
“…The absence of PHOX2B mutations in individuals with ROHHAD, despite its clinical similarity to CCHS, suggests that other genes or regulatory sequences may be associated with autonomic function and NB pathogenesis (89).…”
Section: Inactivating Mutations In Phox2bmentioning
confidence: 99%
“…16 It was later confirmed that none of these 8 genes or RAI1 gene were major ROHHAD genes. 17 In our case, none of the tested genes were positive. A negative test could be due to variation in the genomic region not covered by the test; or due to large insertions, deletions, duplications, inversions, complex rearrangements which cannot be detected.…”
Section: 2mentioning
confidence: 94%
“…Use of patients' neuroendocrine tumour represents one approach to address this challenge. 17 Hence unambiguous identification of ROHHAD syndrome has been challenging; confirmatory laboratory testing is not yet available, and the patient population may represent heterogeneous group of underlying etiologies. Hence emphasis on diagnosis based on clinical findings.…”
Section: 2mentioning
confidence: 99%
“…Less severe phenotypes associated with PARMs such as 20/24 and a subset of 20/25 cases, may lead to a delayed diagnosis until later in childhood or in adulthood, when this condition may be unmasked after pneumonia or administration of sedatives or anesthetics . ROHHAD typically presents in early childhood (1.5‐7 years old) with rapid weight gain of 20‐30 pounds over a 3‐6 month period, and a phenotype that “unfolds” over time including severe alveolar hypoventilation; it has no identified genetic basis at present, despite aggressive inquiry . In both patient populations, surgically implanted diaphragmatic pacemakers decrease the need for constant mechanical ventilation by stimulating the phrenic nerve to ensure regular breathing for up to 12‐15 hours per day …”
Section: Introductionmentioning
confidence: 99%
“…1 ROHHAD typically presents in early childhood (1.5-7 years old) with rapid weight gain of 20-30 pounds over a 3-6 month period, and a phenotype that "unfolds" over time including severe alveolar hypoventilation; it has no identified genetic basis at present, despite aggressive inquiry. [5][6][7] In both patient populations, surgically implanted diaphragmatic pacemakers decrease the need for constant mechanical ventilation by stimulating the phrenic nerve to ensure regular breathing for up to 12-15 hours per day. 8,9 Phrenic nerve-diaphragm pacemakers can be life-changing for patients who require continuous artificial ventilation, allowing them to lead physically active lives with exertion in moderation without being tethered to a ventilator during the day (Figure 1).…”
mentioning
confidence: 99%